Optimization of solid-state fermentation conditions for high β-galactosidase-producing lactic acid bacteria and its application in low-lactose dairy products - Zhang, Zhanjia (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionLactose intolerance affects 85%–95% of Chinese adults, creating substantial demand for low-lactose dairy products. This study aimed to develop a cost-effective β-galactosidase production process through solid-state fermentation (SSF) using agricultural byproducts.MethodsA high-yielding strain was isolated from Tibetan fermented yak milk and identified through morphological, biochemical, and 16S rDNA sequence analysis. Solid-state fermentation conditions were optimized using single-factor experiments and Box-Behnken response surface methodology. Enzymatic properties were characterized, and the enzyme was applied to milk lactose hydrolysis. Techno-economic and environmental impact analyses were conducted.ResultsLactobacillus plantarum LP-15 exhibited initial enzyme activity of 44.7 U/g. Optimal SSF conditions were determined as substrate ratio of wheat bran:soybean meal:whey powder (6:3:1), 37 °C, pH 6.5, and 55% moisture content, achieving enzyme activity of 186.3 U/g (4.17-fold improvement). The enzyme exhibited optimal activity at pH 6.5 and 42 °C, with Km of 2.8 mM and catalytic efficiency of 5.3 × 104 M−1s−1. Milk lactose was reduced by 81.9% within 4 h using 2.0 U/mL enzyme at 40 °C, meeting the low-lactose standard (≤0.1%). SSF reduced production costs by 35.7%, water usage by 94%, and CO2 emissions by 62.4% compared to liquid fermentation.DiscussionThis study provides an economically viable and environmentally sustainable solution for low-lactose dairy production in China, establishing independent intellectual property rights while addressing nutritional needs of lactose-intolerant populations through circular utilization of agricultural by products.